2012
DOI: 10.1094/pdis-10-11-0890-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Heterobasidion annosum on Pinus pinaster in Spain

Abstract: The basidiomycete Heterobasidion annosum (Fr.) Bref. (=Fomes annosus (Fr.) Cooke), one of the most important pathogens in coniferous forests in Europe, Asia, and North America, causes root and butt rot. H. annosum was first recorded on Pinus pinaster Ait. (commonly known as Maritime pine) in France and Great Britain in 1961 (4) and Portugal in 1986 (2). P. pinaster is the most widespread conifer in Spain, with more than 700,000 and 600,000 ha in pure and mixed stands, respectively. Over the last few years, P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, we should take into account the possibility that the present state of the decline may be due to a complex relationship between fungal (Ophiostoma minus, Heterobasidion annosum, recently detected in some areas close to our sampling plots (Prieto-Recio et al, 2012), or even other pathogens as Phytophthora cinnamomi...), soil, climatic and silvicultural factors. Anyway, further work is necessary to determine the pathogenicity of O. minus and other associated ophiostomatoids fungi on adult trees, with the aim to definitively establish the association of this fungus with the maritime pine decline.…”
Section: Discussionmentioning
confidence: 99%
“…However, we should take into account the possibility that the present state of the decline may be due to a complex relationship between fungal (Ophiostoma minus, Heterobasidion annosum, recently detected in some areas close to our sampling plots (Prieto-Recio et al, 2012), or even other pathogens as Phytophthora cinnamomi...), soil, climatic and silvicultural factors. Anyway, further work is necessary to determine the pathogenicity of O. minus and other associated ophiostomatoids fungi on adult trees, with the aim to definitively establish the association of this fungus with the maritime pine decline.…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish isolates of Heterobasidion used in the study (H1 and H4) were previously isolated and identified as H. annosum s. s. (Prieto-Recio et al 2012). The Spanish isolates of Heterobasidion used in the study (H1 and H4) were previously isolated and identified as H. annosum s. s. (Prieto-Recio et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 120 two-year-old P. pinaster seedlings (Meseta Castellana provenance, Spain) were obtained from a Government tree nursery in Castile and Leon. The Spanish isolates of Heterobasidion used in the study (H1 and H4) were previously isolated and identified as H. annosum s. s. (Prieto-Recio et al 2012). The sequences were deposited in the EMBL/GenBank database (GenBank Accession No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations